From Theory to Practice: Implementing Ta'limul Muta'allim in Modern Education Systems - Asbari, Danish Akbar Firdausy; Asbari, Raihan Arsyad Firdausy; Nurhayati, Wakhida; Asbari, Masduki (IJOSMAS, 2024)
This study examines the impact of Burhanuddin Az-Zarnuji's classical educational text,